Determinants of Lending Behavior: Empirical Evidence from Iraqi Private Banks - Kareem, Sana Simko; Mohammad, Shivan Ahmed (Kerbala International Journal of Management and Economics, 2025)
This explanation investigates the determinants of lending behavior of 18 commercial banks listed in the Iraq Stock Exchange between a period of 2014-2023. The research’s goal is to identify the most important things that affect how banks perform, the choices of banks to lend loans and examining how different factors affect the way banks give out loans in an economy that’s affected by war, violence or political conflict. The researchers are using statistical methods or way to measure the relationship between two variables and simple regression techniques to look into the relationship between lending behavior (measured in loans and advances) and three key determinants carefully and in detail. The three ley determinants are: liquidity ratio, bank size and deposit ratio. The detailed examination is based on well-known and trusted theories that are already accepted, including credit market theory, loan pricing theory and money creation theory. The findings reveal that while all independent variables result in research that are reliable and not random variation using statistical tests with the relationships with lending behavior, the connection is relatively weak with the model explaining only 3% of difference in lending pattern. Reverse to theoretical expectations, liquidity ratio shows a bad connection with loans and advances, while deposits ratio shows positive a linkage with loan activity. The study says that classical determinants of loan activity may not fully explain Iraqi banking industry behavior, mainly because of the unstable of the political situation and economy. The research delivers key insights into banking behavior in emerging economies under external pressure and suggests that unique regional problems require more detailed approaches to banking analysis and regulation.